KAJIAN KERETAKAN DRUM BAGIAN ATAS PADA KETEL UAP PIPA AIR - Purwo Subekti; Sunarno - (Jurnal APTEK, 2010)
Boiler tube basically consists of (drum), which closed at the end of the trial stem, where on the inside of the drum there are pipes that serves to drain water or hot gases. In boiler operations are expected not to crash (damage) but the fact is still an interruption in its operations, this led to the cessation of company activities that result in the loss to be borne by the company. The purpose of this study was to analyze the condition of the boiler drum upper material that has been operating in the intervening 10 years. Microstructural examination showed that the damage (cracks) that occur are due to stress corrosion cracking (SCC), as characterized by the formation of the branched cracks (cracks braching). Factors cause of SCC is the tensile stress flow equally with corrosive environment. Residual voltage source is from the welding process in the boiler drum during plugging. In addition, residual stress may also occur due to the influence of corrosive environment forming. And cold, is caused by the influence of boiler feed water. SCC due to KOH (caustic) can be avoided by not doing the welding in the drum, and adjust the pH to be safe areas.